Self-(in)compatibility in sour cherry (Prunus cerasus L.). A minireview - Hegedűs, A. (International Journal of Horticultural Science, 2006)
Sour cherry (Prunus cerasus L.) is an allotetraploid species derived from hybridisation of the diploid sweet cherry (P avium L.) and the tetraploid ground cherry (P. fruticosa Pall.). Although numerous self-incompatible cultivars exist, the most sour cherry cultivars are self-compatible, which might be due to their tetraploid nature. This review is dedicated to show the limited information on the genetics of self-incompatibility in sour cherry accumulated during the last five years. Two different hypotheses (genomic arrangement of the alleles or the accumulation of non-functional S-haplotypes) are discussed. Heteroallelic sour cherry pollen was shown to be self-incompatible, which is counter to the Solanaceae where heteroallelic pollen frequently self-compatible due to a kind of competitive interaction between the two different alleles. This review highlights some inconsistencies in the hope that clarification will be achieved in the near future.